2016
DOI: 10.4103/2303-9027.175876
|View full text |Cite
|
Sign up to set email alerts
|

The role of endoscopic ultrasound in pancreatic cancer screening

Abstract: Pancreatic cancer (PC) is a highly lethal cancer. Despite a significant advancement in cancer treatment, the mortality rate of PC is nearly identical to the incidence rates. Early detection of tumor or its precursor lesions with dysplasia may be the most effective approach to improve survival. Screening strategies should include identification of the population at high risk of developing PC, and an intense application of screening tools with adequate sensitivity to detect PC at an early curable stage. Endoscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 79 publications
0
30
0
3
Order By: Relevance
“…Solid pancreatic lesions (SPL) are mostly malignant with 5-year survival rates of less than 5%[ 1 ]. Endoscopic ultrasound guided fine needle aspiration (EUS-FNA) is a very good tool for the diagnosis of malignant SPL, with sensitivity and specificity rates of 91% and 94%, respectively[ 2 , 3 ], but it shows false negative results in approximately 15% of cases[ 4 ]. Strict follow up for negative FNA lesions is mandatory and may necessitate the use of invasive techniques to reach a full diagnosis, such as diagnostic laparoscopy[ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Solid pancreatic lesions (SPL) are mostly malignant with 5-year survival rates of less than 5%[ 1 ]. Endoscopic ultrasound guided fine needle aspiration (EUS-FNA) is a very good tool for the diagnosis of malignant SPL, with sensitivity and specificity rates of 91% and 94%, respectively[ 2 , 3 ], but it shows false negative results in approximately 15% of cases[ 4 ]. Strict follow up for negative FNA lesions is mandatory and may necessitate the use of invasive techniques to reach a full diagnosis, such as diagnostic laparoscopy[ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The sensitivity and specificity of tumor marker CA19-9 in the diagnosis of pancreatic cancer are 79%-81% and 82%-90%, respectively. However, about 3%-7% of pancreatic cancer patients are Lewis antigen negative and also do not express CA19-9; abnormal CA19-9 levels are not detected in this type of patients[ 20 , 36 , 37 ]. In this study, serum levels of circ-LDLRAD3 were found to be closely related to blood CA19-9 levels.…”
Section: Discussionmentioning
confidence: 99%
“…However, EUS has become the most sensitive examination for PC in patients with clinical manifestations suggesting PC or high-risk factors for PC. Moreover, EUS-guided fine needle aspiration can confirm the diagnosis of PC by puncturing pancreatic lesions through the gastrointestinal tract wall [ 46 ].…”
Section: Diagnostic Endoscopic Techniquementioning
confidence: 99%